Visibility of LEO satellites under different ground network distributions - Wang, Kan; Yang, Xuhai; El-Mowafy, Ahmed (2022)
The Low Earth Orbit (LEO) satellites have shown various benefits in augmenting the Positioning, Navigation and Timing (PNT) service based on Global Navigation Satellite Systems (GNSSs). The higher number of LEO satellites and their much smaller footprints than those of the GNSS satellites motivate studies of the ground tracking network design to pursue higher visibilities to LEO satellites. This contribution proposes an algorithm, called here ‘MaxVis’ to select network stations for LEO satellites of different inclinations and altitudes. The goal is to increase the general visibility and shorten the visibility gaps of LEO satellite that can be observed from the entire ground network, i.e., when at least one of the network stations are visible to the satellite. A parameter can be set to balance the priority of the two objectives. It was found that LEO satellites with high altitudes and low inclinations tend to deliver high visibility. With only the polar regions excluded from the design area for demonstration purposes, the general visibility could reach above 98% with less than 30 stations when the LEO satellite has an altitude of 1200 km and an inclination of 50 degrees. The visibility could be significantly reduced when island areas are excluded from the design area.